Resistance to aflatoxin accumulation in kernels of maize inbreds selected for ear rot resistance in West and Central Africa - Brown, R.L.; Chen, Z.Y.; Menkir, A.; Cleveland, T.E.; Cardwell, K.; Kling, J.; White, D.G. (Elsevier, 2001)
Thirty-six inbred lines selected in West and Central Africa for moderate to high resistance to maize ear rot under conditions of severe natural infection were screened for resistance to aflatoxin contamination using the previously established kernel screening assay. Results showed that more than half the inbreds accumulated aflatoxins at levels as low as or lower than the resistant U.S. lines GT-MAS:gk or MI82. In 10 selected aflatoxin-resistant or aflatoxin-susceptible inbreds, Aspergillus flavus growth, which was quantified using an A. flavus transformant containing a GUS-β-tubulin reporter gene construct, was, in general, positively related to aflatoxin accumulation. However, one aflatoxin-resistant inbred supported a relatively high level of fungal infection, whereas two susceptibles supported relatively low fungal infection. When kernels of the 10 tested lines were profiled for proteins using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, significant variations from protein profiles of U.S. lines were observed. Confirmation of resistance in promising African lines in field trials may significantly broaden the resistant germplasm base available for managing aflatoxin contamination through breeding approaches. Biochemical resistance markers different from those being identified and characterized in U.S. genotypes, such as ones inhibitory to aflatoxin biosynthesis rather than to fungal infection, may also be identified in African lines. These discoveries could significantly enhance the host resistance strategy of pyramiding different traits into agronomically useful maize germplasm to control aflatoxin contamination.